PENGARUH REKRUTMEN DAN SELEKSI TERHADAP KINERJA KEPALA MADRASAH IBTIDAIYAH NEGERI (MIN) SEKOTA BANDAR LAMPUNG - Patimah, Siti (SCAD Independent, 2015)
Education institutions play a strategic role as an institution that serves to prepare qualified human resources to face the challenges of change of the association world, in particular the progress of a society that is triggered by the development of science, technology and art. Educational institutions run by the old paradigm that is focused on the quantity, needs to be changed and directed to the vision and mission to participate actively and proactively prepare for a product or service quality education. The problems that often arise in the process is the low quality of human resources in education management. If the scope of schooling is still low quality of teachers and principals. The school principal is one component that was instrumental has a very strategic position. The decline in the quality of education schools in Indonesia caused by the low level of professionalism of the principal as education manager at the field level. Low level of professionalism in them due to the still weak in the appointment of principals. This study focused on the recruitment and selection of the Head of State Elementary School in Bandar Lampung.